EFEKTIVITAS JOGJA HALAL FEST DALAM UPAYA MEMBANGUN LITERASI GAYA HIDUP HALAL - Aljufri, Ahmad Fadhil; Muslim, Aziz (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2023)
Literacy through event organizers is very common in society, including at the Jogja Halal Fest event. The benefits and influences of the event are to echo and promote the halal lifestyle which has become a current trend. This activity is expected to reduce public ignorance, especially residents of Yogyakarta Special Region, in accessing information regarding issues of halal lifestyle trends. By holding this event, it is hoped that knowledge regarding halal lifestyle literacy will increase. Therefore the author intends to confirm that one way to build halal lifestyle literacy is by holding a Halal Jogja fest event. This research was conducted using a qualitative research and data collection method, namely observation, in-depth interviews and literature that cannot be achieved (obtained) by means of statistical quantification or other (measurement). The Jogja Halal Festival event is an alternative for literacy activities on halal lifestyle trends. Various activities and exhibitions of halal products at the Jogja Halal Festival event are enough to satisfy the public in obtaining information regarding halal lifestyle trends so that they became one of the greatest effective literacy media through analysis of effectiveness theory.